2020
DOI: 10.1021/acs.jafc.0c01877
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Emulsion and Nanoemulsion Delivery Systems: The Chemical Stability of Curcumin Decreases as Oil Droplet Size Decreases

Abstract: The water dispersibility, chemical stability, and bioaccessibility of curcumin, a labile hydrophobic nutraceutical, can be enhanced by incorporating it inside the oil droplets of oil-in-water emulsions or nanoemulsions. In these multiphase systems, the curcumin remains relatively stable to degradation when surrounded by oil but degrades rapidly when surrounded by water. We hypothesized that the size of the lipid droplets would therefore impact the stability of encapsulated curcumin by altering the surface area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 36 publications
1
21
1
Order By: Relevance
“…Another promising application of nanoemulsions is to enhance the bioaccessibility and bioavailability of hydrophobic bioactive compounds [18]. In vitro studies using simulated gastrointestinal models have shown that nanoemulsions can increase the bioaccessibility of β-carotene [19,20], lycopene [21], resveratrol [22], curcumin [23][24][25][26], and 5-demethylnobiletin [27]. Information about the preparation procedures and droplet sizes of nanoemulsions used for different applications is summarized in Table 1.…”
Section: Nanoemulsionsmentioning
confidence: 99%
“…Another promising application of nanoemulsions is to enhance the bioaccessibility and bioavailability of hydrophobic bioactive compounds [18]. In vitro studies using simulated gastrointestinal models have shown that nanoemulsions can increase the bioaccessibility of β-carotene [19,20], lycopene [21], resveratrol [22], curcumin [23][24][25][26], and 5-demethylnobiletin [27]. Information about the preparation procedures and droplet sizes of nanoemulsions used for different applications is summarized in Table 1.…”
Section: Nanoemulsionsmentioning
confidence: 99%
“…In another study, Kharat and co-workers [ 116 ] considered the effect of droplet surface area on the kinetics of CUR degradation using emulsions with different mean droplet diameters. The authors observed that the rate of CUR degradation increased with decreasing droplet size, and they concluded that this was attributable to the fact that CUR exchange between the interior and exterior was faster in small droplets.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…The authors postulated that droplet size plays the most important role in the degradation of curcumin encapsulated in emulsions; a fact that may affect its bioactivity in various food and beverage products. Resveratrol’s chemical stability may be increased by its incorporation into nanoemulsion compared with that of free (aqueous or ethanolic extract) resveratrol [ 358 ]. Phytosterols, such as stigmasterol, β-sitosterol and campesterol, have been proved to inhibit the absorption of dietary cholesterol but demonstrate degradation issues related to oxidation [ 359 ].…”
Section: Organic-based Delivery Systemsmentioning
confidence: 99%